Analisis Manajemen Risiko pada UMKM Melina Helm - Aris Kurniawan; Dhafin Al-Rasyid Sastradireja; Ghulam Yoniar Priatna; Reihan Ahmad Nurhakim; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management in UMKM Melina Helm by applying the SWOT analysis approach to identify, assess, and control risks that may affect business sustainability. As an SNI-certified helmet manufacturer, Melina Helm faces various risks, including market, operational, human resource, financial, security, and legal risks. This research uses a qualitative method with a case study approach supported by observations and interviews. The results show that market risks, particularly intense price competition and declining consumer purchasing power, are classified as high risks due to their direct impact on sales performance. Operational risks such as supply delays and inconsistent product quality also fall into the high-risk category because they disrupt production efficiency. Meanwhile, risks related to human resources, security, and finance are categorized as medium to high and require structured risk control. The SWOT analysis reveals key strengths, especially product quality and innovative design, while major threats originate from tight competition and counterfeit products. This study concludes that integrating risk management with SWOT analysis provides an effective strategy to strengthen risk mitigation and enhance business sustainability